Challenges in the diagnosis of cutaneous adnexal tumours. Issue 12 (23rd November 2015) - Danialan, Richard; Mutyambizi, Kudakwashe; Aung, Phyu; Prieto, Victor G; Ivan, Doina
Abstract : The diagnosis of cutaneous adnexal neoplasms, a heterogeneous group of entities, is often perceived by practising pathologists as challenging. A systematic approach to diagnosis is necessary for classification of these lesions, which establishes the tumour differentiation (follicular, sebaceous, sweat gland or apocrine) and evaluates histological features differentiating between benign and malignant entities. Consideration of clinical history is a necessary adjunct in evaluation of the adnexal neoplasm, as characteristic anatomical sites are described for many adnexal lesions. In some instances, immunohistochemical studies may also be employed to aid the diagnosis. The differential diagnosis between primary cutaneous adnexal neoplasms and cutaneous metastases from visceral tumours may also be difficult. Clinical, radiological, histological and immunohistochemical characteristics will be further discussed, considering that the correct diagnosis has a significant impact on the patient's management and prognosis.